The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21203/rs.3.rs-79490/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bidirectional association of neurodevelopment with growth: A Prospective Cohort Study

Abstract: Background Evidence of the association between early life development in neurological and psychiatric with physical growth is controversial, and bidirectional effects have been poorly evaluated. The study aims to use the cross-lagged models and utilize data from the Born in Shenyang Cohort Study to characterize the bidirectional associations of the term-born infants' development in neurological and psychiatric in five domains and physical growth in the early life. Methods This study consists of 688 mother-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The Gesell Development Diagnosis Scale (GDDS) was developed in 1925 and widely used (Gesell 1925). The GDDS is a classic neuropsychological development examination and widely used in children aged 0 to 60 months, including 5 domains: gross motor, fine motor, adaptability, language, and social skills (Jin et al 2007; You et al 2019; Wei et al 2021). The GDDS was used in a retrospective study of pediatric recipients and the results showed that preoperative developmental levels were related to improvements in auditory perception and speech production by parent-report scales after CI surgery (Yang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Gesell Development Diagnosis Scale (GDDS) was developed in 1925 and widely used (Gesell 1925). The GDDS is a classic neuropsychological development examination and widely used in children aged 0 to 60 months, including 5 domains: gross motor, fine motor, adaptability, language, and social skills (Jin et al 2007; You et al 2019; Wei et al 2021). The GDDS was used in a retrospective study of pediatric recipients and the results showed that preoperative developmental levels were related to improvements in auditory perception and speech production by parent-report scales after CI surgery (Yang et al 2017).…”
Section: Introductionmentioning
confidence: 99%